Characteristics associated with US Walk to School programs - Neelon Brian; Vaughn Amber; Linnan Laura; Ward Dianne S; Martin Sarah L; Fulton Janet E (BMC, 2007)
Abstract Participation in Walk to School (WTS) programs has grown substantially in the US since its inception; however, no attempt has been made to systematically describe program use or factors associated with implementation of environment/policy changes. Objective Describe the characteristics of schools' WTS programs by level of implementation. Methods Representatives from 450 schools from 42 states completed a survey about their WTS program's infrastructure and activities, and perceived impact on walking to school. Level of implementation was determined from a single question to which respondents reported participation in WTS Day only (low), WTS Day and additional programs (medium), or making policy/environmental change (high). Results The final model showed number of community groups involved was positively associated with higher level of implementation (OR = 1.78, 95%CI = 1.44, 2.18), as was funding (OR = 1.56, 95%CI = 1.26, 1.92), years of participation (OR = 1.44, 95% CI = 1.23, 1.70), and use of a walkability assessment (OR = 3.22, 95%CI = 1.84, 5.64). Implementation level was modestly associated with increased walking (r = 0.18). Conclusion Strong community involvement, some funding, repeat participation, and environmental audits are associated with progms that adopt environmental/policy change, and seem to facilitate walking to school.